Argumentación jurídica del principio de imparcialidad en los procesos penales y su incidencia en los derechos fundamentales de las personas - Bermudez Castro, Jorge Luis (2016)
This theme that says "legal argumentation of the principle of fairness in criminal proceedings and their impact on the fundamental rights of the people" is of vital importance at national and international level, since it is expected that through this research is not sacrificed the justice on behalf of supposed interests of legal efficiency, factors affecting the misapplication of the basic guarantees of due process in criminal matters, and the violation of human rights in legal proceedings that have been widespread in our increasingly globalized . Due process is a fundamental right binding for the actions of the courts, in a struggle for the defense of the rights of citizens; criminal proceedings where basic guarantees enshrined in our Constitution are respected. Each and every one of the techniques that were used to collect data and information in this investigation, related to the legal argument of the principle of fairness in criminal proceedings and their impact on the fundamental rights of people.